The semiotics of written discourse and the dual representation of information in memory: an application of nonverbal elements to FL reading methodology - Reinildes Dias (1985)
This dissertation advocates a recurrent and systematic use of nonverbal elements, as well as pictorial information incorporated into the reading lesson, to initiate linguistic activity in the teaching of FL reading. For this purpose, two broad avenues are brought to bear. The first is discourse-oriented and includes an expanded review of the structure of the written text with its two basic semiotic devices, the verbal and nonverbal ones. The second is cognition-oriented and includes a review of two important issues, namely, the information-processing system and the concept of sdiema. These two cognitive issues inform the view this dissertation adopts of comprehension as an interactive process which involves both text-presented material and the information the reader brings to the reading task in the form of previous knowledge. Still within cognitive psychology another issue is discussed, namely, Paivio's dual-coding theory, which provides the specific theoretical basis for the major argument of this dissertation. Paivio's theory of memory comprises verbal and nonverbal representations and fits in neatly with the structure of written discourse. All theoretical issues are finally translated into suggestions of activities for each phase of a reading lesson. The underlying purpose is to bridge theory and practice towards a more efficient FL reading methodology for high-school students.